INTERNET MEMES AS PUBLIC POLICY INSTRUMENTS - V. А. Glukhikh; S. M. Elisejev (Дискурс, 2017)
The tendency to reduce electoral activity is one of the acute problems in the sphere of political relations. This trend can be observed not only in the countries of the new, but also in the "old" democracy. Models of economic and political behavior are changing with the development of the information society. People spend more and more time in social networks, plunging into virtual reality, going away from problems of social reality or first-order reality. The problem of using Internet memes in election companies is studied here. This phenomenon has emerged relatively recently and represents a new tendency in modern politics. The main ideas of the theory of memes and the practice of their use in modern politics are briefly described in the article.